2013
DOI: 10.1111/j.1742-7843.2012.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Attenuates Chronic Methamphetamine‐induced Pulmonary Arterial Remodelling: Possible Involvement of Serotonin Transporter and Serotonin 1B Receptor

Abstract: Epidemiological data have shown that methamphetamine (MA) abuse significantly increases the risk of developing pulmonary arterial hypertension (PAH). To investigate whether MA could induce PAH and its possible mechanism, rats were exposed daily to MA for 5 weeks in the absence or presence of fluoxetine. The results showed that the pulmonary arterial pressure was not significantly increased, but the pulmonary arterial remodelling was markedly developed in the MA exposure group. The protein expressions of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…On day 22, the rats in all the groups were anaesthetized with 3% pentobarbital sodium (40 mg/ kg). Systemic arterial pressure (SAP) and pulmonary arterial pressure (PAP) were recorded under the same conditions as previously described (22)(23)(24). The right carotid artery was isolated and cannulated with a polyethylene catheter to a fluid-filled force transducer.…”
Section: Assessment Of Pahmentioning
confidence: 99%
See 2 more Smart Citations
“…On day 22, the rats in all the groups were anaesthetized with 3% pentobarbital sodium (40 mg/ kg). Systemic arterial pressure (SAP) and pulmonary arterial pressure (PAP) were recorded under the same conditions as previously described (22)(23)(24). The right carotid artery was isolated and cannulated with a polyethylene catheter to a fluid-filled force transducer.…”
Section: Assessment Of Pahmentioning
confidence: 99%
“…The pulmonary arteries (external diameter, 60-80 µm) were randomly selected for high-power (x400) evaluation. Pulmonary vascular remodeling was measured as the percentage of medial thickness, which was calculated according to previously described methods as follows: medial wall thickness (%) = (external diameter -internal diameter)/ external diameter) x100% (22); wall area (%) = (total vessel area -lumen area)/total vessel area x100% (25).…”
Section: Assessment Of Pahmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study (11) reported that the inhibition of 5-HTR2a and 5-HTR2b had no effect on efferocytosis, although inhibiting SERT prevented 5-HT-impaired efferocytosis. A previous epidemiological study (12) suggested that MA abuse significantly increased the risk of developing pulmonary arterial hypertension (PAH). The disease severity and susceptibility to PAH may be associated with the increased SERT activity (13).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the 5-HT reuptake inhibition mediated by fluoxetine is also likely to be effective in animal models of obsessive--compulsive disorder (OCD) [91], panic-like behaviour [92], as well as in bulimia and anorexia nervosa [93]. Indeed, this drug was observed to be effective in pulmonary vascular remodelling induced by methamphetamine [94] and in relieving premenstrual syndrome [95]. However, like other findings with SSRI, fluoxetine had no effect reversing pain-related behaviours [96].…”
Section: Other Preclinical Studiesmentioning
confidence: 99%